Comparison between HET-CAM protocols and a product use clinical study for eye irritation evaluation of personal care products including cosmetics according to their surfactant composition. (July 2021) - Rivero, Martín Nicolás; Lenze, Mariela; Izaguirre, Mercedes; Pérez Damonte, Silvia H; Aguilar, Alejandro; Wikinski, Silvia; Gutiérrez, María Laura
Abstract: The hen's egg test on chorioallantoic membrane (HET-CAM) is one of the most frequently used alternative tests for prediction of ocular irritation of cosmetic products. There are different HET-CAM protocols widely accepted, but there is no information about which of the protocols better correlates with the results obtained in product use clinical study under the conditions of use. Two Fix Time Methods (FTM) -Lüepke and the ICCVAM guideline - and two Reaction Time Methods (RTM) -ECVAM DBALM Prot. No. 47 and No. 96- were employed to test 18 cosmetic products. Simultaneously, they were evaluated by an ophthalmological clinical test. A unified classification system was used, and products were classified into four irritation levels: non-irritant, weak, moderate and severe irritant. The duration of use (rinse-off or leave-on), and the concentration and type of surfactants were taken into account in the analysis. All the products that were classified as non-irritant by any HET-CAM protocols were also safe in the product use clinical study. The product that was found to be non-safe in the product use clinical evaluation was also unsuitable by most of the HET-CAM protocols. These results were employed to develop an algorithm that allows selecting the appropriate HET-CAM protocol for each type of product to be tested. Highlights: Cosmetic surfactant type and concentration orientate HET-CAM protocol selection. HET-CAM is suitable for predict eye irritation induced by leave-on products. HET-CAM is useful to evaluate shampoos at 10% dilution with non-ionic surfactants. HET-CAM is useful to evaluate rinse-off products with low surfactant concentration. HET-CAM is not reliable for products with high concentration of anionic or cationic surfactants.